Methods of supply of nitrogen to improve productivity in the culture of irrigated beans in savanna mato-grossense - Lange, Anderson; Cavalli, Edilson; Carleto, Ewerton Alves; Buchelt, Antonio Carlos [UNESP]; Cavalli, Cassiano; Pereira, Cassiano Spaziani (Univ Federal Mato Grosso, 2018)
Nitrogen is one of the elements most required by the bean crop and its supply to the plant can occur through nitrogen fertilization and through biological fixation. The objective of this study was to evaluate strategies of nitrogen fertilization management and the ability of the association between inoculant and Co + Mo to partially replace the N applied in the bean crop planted in irrigated system. The study was developed in Sinop-MT, from June to October 2011, a period denominated winter, under central pivot in a no-tillage system, in a Red-yellow Latosol. The experimental design was a randomized block with 15 treatments and 4 replicates. The treatments consisted of the combination of rates and sources of N, inoculation with Rhizobium tropicci and treatment of seeds with Co and Mo. Regarding the treatments, no difference was observed in the height of the first pod insertion and number of grains per pod. The productivity was higher in the treatments that received N. The association of the inoculation with low rates of N is effective to meet the demands of the crop, equaling to high rates of N. The productivity showed a positive and significant correlation with most of the evaluated characteristics.
Keywords: Phaseolus vulgaris; management of nitrogen; direct sowing in straw; biological nitrogen fixation; winter cropping